Nanoindentation Characterization on Microhardness of Micron-Level TiC and TiB Reinforcements in in-situ Synthesized (TiC+TiB)/Ti-6Al-4V Composite - Wen, Yan; Guo, Tingting; Zhou, Yuangui; Bai, Huiping; Wang, Zhou (Frontiers in Materials, 2019)
The microhardness of micro-level TiC and TiB reinforcements in in-situ synthesized (TiC+TiB)/Ti-6Al-4V composite were investigated independently by spherical nanoindentation. The morphology of indentation on the matrix, reinforcements and the reinforcement / matrix interfaces were characterized by scanning electron microscope (SEM). The influence of cracks on the load-displacement curves and microhardness were analysed and discussed. The microhardness of TiC and TiB were calculated from the load-displacement curves on reinforcements without cracks. The average microhardness of TiC and TiB in this composite were 24.1 and 19.6 GPa, respectively, which agreed with the values in other composites and coatings. These results verified that the nanoindentation method was a very useful method to characterize the microhardness of micron-level reinforcements in discontinuous metal matrix composite.